2016
DOI: 10.1016/j.jbiomech.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Digital volume correlation can be used to estimate local strains in natural and augmented vertebrae: An organ-level study

Abstract: Digital Volume Correlation (DVC) has become popular for measuring the strain distribution inside bone structures. A number of methodological questions are still open: the reliability of DVC to investigate augmented bone tissue, the variability of the errors between different specimens of the same type, the distribution of measurement errors inside a bone, and the possible presence of preferential directions. To address these issues, five augmented and five natural porcine vertebrae were subjected to repeated z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 23 publications
2
45
0
Order By: Relevance
“…To overcome to the first limitation, we suggest to publish in the public domain the images used to test the DVC precision in the different publications. We started this process in previous studies (Palanca et al, 2016;Tozzi et al, 2017;Palanca et al, 2017a) and we suggest that also future publications should share the input datasets or use the published images as benchmark. The reader is encourage to look at the figshare links in the acknowledgments for the complete or partial datasets used in the presented studies and contact the corresponding author for the complete datasets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome to the first limitation, we suggest to publish in the public domain the images used to test the DVC precision in the different publications. We started this process in previous studies (Palanca et al, 2016;Tozzi et al, 2017;Palanca et al, 2017a) and we suggest that also future publications should share the input datasets or use the published images as benchmark. The reader is encourage to look at the figshare links in the acknowledgments for the complete or partial datasets used in the presented studies and contact the corresponding author for the complete datasets.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the previously examined datasets consist in results from trabecular and cortical bone scanned with μCT (Dall ' Ara et al, 2014;Palanca et al, 2015) and with synchrotron light μCT (SRμCT) (Palanca et al, 2017a), from vertebral bodies with and without injected biomaterial scanned with μCT (Palanca et al, 2016;Tozzi et al, 2017), and mice tibiae scanned with SRμCT (Palanca et al, 2017a). Moreover, two new datasets from SRμCT scans of trabecular bone and biomaterials and from in vivo and ex vivo μCT scans of the mouse tibia were included in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DVC grid is then converted into an 8-noded hexahedral mesh, the displacement field measured from DVC is imposed to the mesh as boundary conditions and is then imported to an FE software package ( ANSYS ® Academic Research, Release 15.0) to compute the strain field. A NS equal to 48voxels (approximately 1872μm) was chosen as the best compromise between precision and spatial resolution of the DVC approach (precision errors below 3.7μm for displacements [40] and approximately 100μɛ for strains [41]).…”
Section: Methodsmentioning
confidence: 99%
“…Let us note that there are few comparisons between local and global approaches to DVC [122,137,169,93,168]. Overall, it is found that the measurement uncertainties are of the same order of magnitude when the total number of kinematic unknowns are similar.…”
Section: Uncertainty Quantificationsmentioning
confidence: 96%